Peran Pendampingan Pastoral dalam Pemulihan Trauma Keluarga Korban Longsor di Palangka dengan Pendekatan Spiritual-Psikologis - Emiliana Javanika Abid Oko; Fitria Ruru; Juliadi Juliadi; Yunice Windia Suba (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
This study aims to explore the role of pastoral care in the recovery of trauma experienced by landslide victim families in Palangka. Pastoral care, which combines spiritual and psychological approaches, is expected to provide holistic support to victim families in their recovery process. This study uses a qualitative method with a case study approach to analyze the experiences and perceptions of victim families and the pastoral caretakers involved. Data were collected through in-depth interviews, observations, and documentation. The results of the study indicate that pastoral care plays an important role in providing emotional and spiritual support, strengthening mental resilience, and helping victim families cope with loss and trauma. The spiritual-psychological approach applied by pastoral caretakers helps rebuild hope, reduce stress, and accelerate the healing process. This study highlights the importance of integrating spiritual and psychological support in post-disaster interventions to improve the mental and emotional well-being of victims.